A Literature Review on Investors’ Perception Towards Mutual Funds with Reference to Performance, Risk - Return, and Awareness - Swain, Prafulla Kumar; Dash, Manoranjan (Indian Journal of Finance, 2017)
The world of finance has witnessed an exponential growth in the post information technology revolution of the 1990s. The present study made an attempt to do a diagnostic analysis of past literature, though a lot of research has been done on investors’ perception on mutual funds. In the present study, literature review on various dimensions with respect to the measurement of performance, risk - return trade off of mutual funds, and investors’ awareness, education, and interest regarding mutual funds was examined to clear the gateway for the upcoming researchers in the field of the mutual fund industry.